Training of English Listening and Speaking Using Virtual Reality Technology - Yang, Qinghua (Journal of the Brazilian Computer Society, 2025)
This paper briefly introduces virtual reality (VR) technology and the basic application process for English listening and speaking training. A case study was conducted with freshmen from the School of Foreign Languages at Hubei University of Science and Technology. The long short-term memory (LSTM) algorithm used for scoring spoken English levels was analyzed and compared with the traditional back-propagation neural network (BPNN) and recurrent neural network (RNN) algorithms. The students were divided into a control group and an experimental group for five-week training. The English listening and speaking levels of these students were tested before and after the training. The results showed that the LSTM algorithm had the highest accuracy and efficiency in scoring spoken English. After the training, the English speaking and listening scores of the students in the experimental group, which used VR technology, were significantly improved.